2021
DOI: 10.17161/kjm.vol14.14984
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Metabolic Surgery Reduced Liver Enzyme Levels in Patients with Non-Alcohol Fatty Liver Disease

Abstract: Introduction. Approximately 93.3 million Americans are obese (BMI>30) and 51% have non-alcoholic fatty liver disease (NAFLD).  Progression of NAFLD can lead to Non-Alcoholic Steatohepatitis (NASH), the leading cause of liver transplant in the United States. This study analyzed liver enzymes following bariatric surgery in NAFLD patients up to one-year post-surgical intervention. Methods. A retrospective analysis of adults with NAFLD who underwent bariatric surgery from 2009 to 2016 was conducted. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The previously mentioned research conducted by Bower et al also confirmed an amelioration in liver enzymes profile, including ALT (11.36 [32]. Groth et al also observed an amelioration in the liver enzymes profile in patients undergoing laparoscopic sleeve gastrectomy during 6 months of follow up (AST 22.0 (19.0-28.0) vs. 16.0 (13.0-22.0), p < 0.001, and ALT 27.5 (20.5-41.0) vs. 19.0 (15.0-27.0), p < 0.001) with no statistical differences regarding gender (p = 0.840) [33].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The previously mentioned research conducted by Bower et al also confirmed an amelioration in liver enzymes profile, including ALT (11.36 [32]. Groth et al also observed an amelioration in the liver enzymes profile in patients undergoing laparoscopic sleeve gastrectomy during 6 months of follow up (AST 22.0 (19.0-28.0) vs. 16.0 (13.0-22.0), p < 0.001, and ALT 27.5 (20.5-41.0) vs. 19.0 (15.0-27.0), p < 0.001) with no statistical differences regarding gender (p = 0.840) [33].…”
Section: Discussionmentioning
confidence: 57%
“…The previously mentioned research conducted by Bower et al also confirmed an amelioration in liver enzymes profile, including ALT (11.36 u/L, 95%CI 8.36–14.39), AST (3.91 u/L, 95%CI 2.23–5.59), ALP (10.55 u/L, 95%CI 4.40–16.70) and gamma-GT (18.39 u/L, 95%CI 12.62–24.16) [ 19 ]. A study conducted by Kirkpatrick et al revealed a reduction in liver enzymes including ALT (66.21 vs. 28.58) and AST (46.28 vs. 24.69) during 12 months of observation [ 32 ]. Groth et al also observed an amelioration in the liver enzymes profile in patients undergoing laparoscopic sleeve gastrectomy during 6 months of follow up (AST 22.0 (19.0–28.0) vs. 16.0 (13.0–22.0), p < 0.001, and ALT 27.5 (20.5–41.0) vs. 19.0 (15.0–27.0), p < 0.001) with no statistical differences regarding gender ( p = 0.840) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%